2009
DOI: 10.1021/cm9013514
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of Epitaxial Magnetite Films and Ferrihydrite Nanoribbons on Single-Crystal Gold

Abstract: Magnetite (Fe3O4), ferrihydrite (Fe10O14(OH)2), and iron (Fe) films were electrodeposited by cathodic deposition from an alkaline Fe(III)−triethanolamine solution. The electrodeposited phase depended on the applied potential. Magnetite films were electrodeposited from −1.01 to −1.10 V vs Ag/AgCl, whereas ferrihydrite films were deposited from −1.10 to −1.20 V vs Ag/AgCl. Iron deposition occurred at more negative potentials. The polycrystalline films were characterized using X-ray diffraction, scanning electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(70 citation statements)
references
References 59 publications
1
69
0
Order By: Relevance
“…16,18) On the contrary, the second reduction wave between ¹1.20 and ¹1.30 V SCE seems to be due to a two-electron process corresponding to the reduction of Fe(II) to Fe.…”
Section: Xps Surface Analysismentioning
confidence: 92%
“…16,18) On the contrary, the second reduction wave between ¹1.20 and ¹1.30 V SCE seems to be due to a two-electron process corresponding to the reduction of Fe(II) to Fe.…”
Section: Xps Surface Analysismentioning
confidence: 92%
“…(1). 12,13) During the initial stage of electrodeposition at ¹1.05 V SCE , increase of the surface area by deposition of magnetite slightly increased the cathodic current density due to the increase of the current. Between ¹1.25 and ¹1.30 V SCE , a two-electron process shows the reduction of Fe(II) to Fe then for more negative potential the increase of the cathodic current density was due to hydrogen gas evolution corresponding to eq.…”
Section: ¹1mentioning
confidence: 99%
“…This corrosion product reduces the efficiency of the steam generator by deterioration of the heat transfer and cause an acceleration of the corrosion of steam generator tube. 13) Hence, its removal improves heat transfer and reduces localized corrosion. 1) Some authors recently presented that the magnetite accelerates the corrosion of the carbon steel by a galvanic coupling.…”
Section: Introductionmentioning
confidence: 99%
“…In this process, the electrochemically produced species reacts with water or hydroxide ions to form a metal oxide on the electrode. [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] A second method to produce thin films is to electrochemically change the pH of the electrolyte at the electrode surface. Because the solubility of any material is dependent on pH, the pH can be electrochemically changed at the electrode surface, thus lowering the solubility of the material and resulting in the precipitation of the material only on the electrode surface.…”
Section: Electrodeposition Of Chiral Filmsmentioning
confidence: 99%
“…Once the nucleation layer is produced, the film maintains the orientation regardless of the precursor. [47] Studies on adsorption of organic molecules on surfaces have shown that local chiral imprinting can be obtained without the need of extended surface Chirality. [6] Adsorption of amino acids on Au [66] and Ag [67] surfaces are reported to be physical in nature, while amino acids chemisorb on Cu single crystals.…”
Section: Electrodeposition Of Chiral Filmsmentioning
confidence: 99%